2018
DOI: 10.3390/app8112041
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in the Absorption and Desorption of CO2 Using Sodium Glycinate Solution

Abstract: This study used sodium glycinate as an absorbent to absorb CO2 in the bubble column scrubber under constant pH and temperature environments to obtain the operating range, CO2 loading, and mass transfer coefficient. For efficient experimentation, the Taguchi method is used for the experimental design. The process parameters are the pH, gas flow rate (Qg), liquid temperature (T), and absorbent concentration (CL). The effects of the parameters on the absorption efficiency, absorption rate, overall mass transfer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
3
19
0
1
Order By: Relevance
“…Table 4 presents the values calculated by Equations (14)- (17), where the range of E is 61.33-100%, RA is 4.02-26.48 × 10 −4 (mol/s.L), KGa is 0.229-0.798(s −1 ), and  is 0.034-0.263 (mole/mole•L). These data are comparable with those reported earlier [42,45,46]. Table 5 showed that the data obtained in this work, such as KGa in the range of 0.229-0.789 s −1 , were higher than that of the sodium glycinate solution (0.051-0.189 s −1 ), the ammonia solution (0.0136-0.3302 s −1 ), the NaOH solution (0.015-0.246 s −1 ), and the MEA solution (0.0377-0.8881 s −1 ).…”
Section: Operation and Data Calculation Of The Steady-state Conditionsupporting
confidence: 93%
See 1 more Smart Citation
“…Table 4 presents the values calculated by Equations (14)- (17), where the range of E is 61.33-100%, RA is 4.02-26.48 × 10 −4 (mol/s.L), KGa is 0.229-0.798(s −1 ), and  is 0.034-0.263 (mole/mole•L). These data are comparable with those reported earlier [42,45,46]. Table 5 showed that the data obtained in this work, such as KGa in the range of 0.229-0.789 s −1 , were higher than that of the sodium glycinate solution (0.051-0.189 s −1 ), the ammonia solution (0.0136-0.3302 s −1 ), the NaOH solution (0.015-0.246 s −1 ), and the MEA solution (0.0377-0.8881 s −1 ).…”
Section: Operation and Data Calculation Of The Steady-state Conditionsupporting
confidence: 93%
“…Therefore, the CO2 of flue gas in a coal-fired power plant at a 15% concentration of and at 50 °C was simulated to enter the column. According to previous works [41,42], the absorption of CO2 in the bubble-column scrubber is affected by the gas flow rate, the liquid flow rate, the concentration of the solvent, as well as the temperature and pH. In order to select the mixed amines, the type of mixed amines (A), the ratio of mixed amines (B), the liquid-flow rate (C), the gas-flow rate (D), and the concentration of mixed amines (E) were considered as the condition factors, and four levels for each condition factor were taken respectively, i.e., the ratio of mixed amine (5-20 wt%), gas-flow rate, Qg, (3-12 L/min), concentration of the mixed amines (1-2.5 M), and the liquid-flow rate, QL, (0.15-0.3 L/min).…”
Section: Absorption Experiments Designmentioning
confidence: 99%
“…The optimization model indicated that the volumetric flow rate of gas and the volumetric flow rate of liquid strongly influenced the absorption efficiency. This was in agreement with the optimization of other absorption systems reported in the literature [7,26]. The precision of this model was verified based on the coefficient of determination (R 2 ) by the parity plot between the experimental and predicted values in terms of the response parameter as shown in Figure 6a.…”
Section: Correlation Modelsupporting
confidence: 89%
“…Among these technologies, an absorption-desorption process for post-combustion has been widely used [1]. A number of solvents have been adopted for the capture of CO 2 [2][3][4]. In these solvents, amines are most extensively used in chemical absorption to capture CO 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the parameter significance and optimization conditions in order to reduce regeneration energy needs was required. This could be done by using the Taguchi experimental design [4,5].…”
Section: Introductionmentioning
confidence: 99%